EFFECT OF BROWN ALGAE (Sargassum Sp) GEL ON ALKALINE PHOSPHATASE LEVELS IN PERIODONTITIS RATS INDUCED BY SILK LIGATION MODEL - Abdurrohman, Muhamat Muhtar S; Muhammad , Faruq Abdurrohman; Sunnah, Tahta Danifatis; Ade Ismail A. K,; Mahardika, Christina (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Periodontitis is a chronic inflammatory disease caused by colonies of dysbiotic bacteria that form biofilms and cause destruction of the periodontal tissues. This damage can be induced by silk ligation on Sprague Dawley teeth and results in an increase in Alkaline Phosphate levels in the gingival sulcus. The purpose of this study was to determine the effect of brown algae extract gel (Sargassum sp) on reducing alkaline phosphatase levels in gingival sulcus fluid in Sprague Dawley periodontitis induced by silk ligation Material and Methods: This research is True Experimental with the Pre test - Post test Control Group Design. The research sample consisted of 36 male Wistar rats which were ligated with silk to periodontitis. Rats were divided into two groups (n=18), the control group was treated with Tie-es metronidazole gel plus and brown algae extract (Sargassum sp) gel treatment with a concentration of 75%. Sampling of gingival sulcus fluid (CSG) on days 0 and 5, ALP levels were measured using a UV/V is spectrophotometer with an absorbance of 450 nm. Results and Discussions: This study showed a decrease in ALP levels after being treated with metronidazole and 75% brown algae extract gel, the normal amount of ALP levels in the reference was 53-57 U/L and increased when inflammation occurred to 8283 U / L then a significant difference was obtained. The average reduction in ALP levels from pre test to post test for each group was 39-41 /L, and there was a significant relationship between giving brown algae extract and a decrease in ALP levels (p <0.05). Conclusion: Brown algae gel extract (Sargassum sp) concentration of 75% has a lowering effect on alkaline phosphatase levels of gingival sulcus fluid in periodontitis induced by silk ligation